Inequality of Ostrowski Type for Mappings with Bounded Fourth Order Partial Derivatives - Waseem Ghazi Alshanti (Abstract and Applied Analysis)
A general Ostrowski’s type inequality for double integrals is given. We utilize function whose partial derivative of order four exists and is bounded.